Cooperative Learning Model and Reading Skills of Middle School Student: Systematic Literature Review - Abdul Bayani (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
Students' reading skills are an important prerequisite in literacy, however, based on the results of the 2018 PISA scores, it has greatly decreased. Many factors affect the decline in students' reading skills, one of which is the learning model applied in the classroom, so this study aims to determine the dominant cooperative learning model affective the reading skills of SMP students. The type of research is literature study with a systematic literature review approach. Data in the form of artefact is collected through searching Google Scholar links with the help of Publish or Perish. Based on the search results, there are as many as 10 artefact used in the study and have met the specified criteria. The results of the analysis obtained that the cooperative learning model can have a positive impact on improving the reading ability or skills of SMP students. The learning models that can be used are TPS, JIGSAW, KWL, CIRC, TTW, and STAD. Each type of cooperative model has advantages and disadvantages, so it is very appropriate to choose a cooperative model in improving the reading skills of SMP students at every grade level.